A Comparison between Beta Trace Protein, Cystatin C and Creatinine for the Estimation of eGFR in Diabetic Nephropathy - Ali, Kamal AL-Deen Hussein; Taher, Aya Yassin (Journal of Science in Medicine and Life, 2024)
BACKGROUND: Diabetes mellitus type 2 is considered the main source of diabetic nephropathy, as the proportion of patients who developed diabetic nephropathy is approximately 45% as a result of type 2 diabetes. It is also considered a cause of kidney patients at the end of the stage. Glomerular filtration rate (GFR) is the best functional parameter for renal diseases. AIM: The aimed of this study was to determine in comparison between Beta Trace Protein, cystatin C and creatinine for the estimation of eGFR in type 2 Diabetic Nephropathy. MATERIALS AND METHODS: A Case-control study included of 120 Persons with T2DM of both gender (40-69 years, 64 males and 56 females), divided into four groups: Group I: includes 30 persons as a healthy control (UACR < 30 mg/g creatinine). Group II: includes 30 patients with type2 DMا normoalbuminuria (اUACR < 30 mg/g creatinine) as a control. Group III: includes 30 patients with type 2 DM microalbuminuria ا(UACR 30 – 300 mg/g creatinine). Group IV: includes 30 patients with type 2 DM macroalbuminuria ا(UACR ˃ 300 mg/g creatinine). RESULTS: the level of GFR ꞵTP is marked decrease than GFR Cystatin C and GFR Cr. in early stage microalbuminuria cumbered with normoalbuminuria group , the results of the current study showed an inverse correlation between BTP and GFR BTP in healthy control group, normalbumin group, microalbumin group and macroalbumin group and a positive correlation between Cystatein C and GFR BTP in normalbumin group, inverse correlation between Cystatein C and GFR Cys.c in healthy control group, normalbumin group, microalbumin group and macroalbumin group and a positive correlation between GFR Cr and GFR Cys.c and GFR BTP in healthy control group, a positive correlation between GFR Cr and GFR Cys.c in normalbumin group and a positive correlation between GFR Cr and GFR BTP in macroalbumin group. CONCLUSION: the level of GFR ꞵTP is better than GFR Cystatin C and GFR Cr. which may be considered as a predictive marker for the estimation of eGFR in type 2 Diabetic Nephropathy.